Ten Novel Mutations in the NR5A1 Gene Cause Disordered Sex Development in 46,XY and Ovarian Insufficiency in 46,XX Individuals - BEREKET, ABDULLAH (ENDOCRINE SOC, 2012)
Context: Steroidogenic factor-1 (SF-1/NR5A1) is a nuclear receptor that regulates adrenal and reproductive development and function. NR5A1 mutations have been detected in 46,XY individuals with disorders of sexual development (DSD) but apparently normal adrenal function and in 46,XX women with normal sexual development yet primary ovarian insufficiency (POI). Objective: A group of 100 46, XY DSD and two POI was studied for NR5A1 mutations and their impact. Design: Clinical, biochemical, histological, genetic, and functional characteristics of the patients with NR5A1 mutations are reported. Setting: Patients were referred from different centers in Spain, Switzerland, and Turkey. Histological and genetic studies were performed in Barcelona, Spain. In vitro studies were performed in Bern, Switzerland. Patients: A total of 65 Spanish and 35 Turkish patients with 46, XY DSD and two Swiss 46, XX patients with POI were investigated. Main Outcome: Ten novel heterozygote NR5A1 mutations were detected and characterized (five missense, one nonsense, three frameshift mutations, and one duplication). Results: The novel NR5A1 mutations were tested in vitro by promoter transactivation assays showing grossly reduced activity for mutations in the DNA binding domain and variably reduced activity for other mutations. Dominant negative effect of the mutations was excluded. We found high variability and thus no apparent genotype-structure-function-phenotype correlation. Histological studies of testes revealed vacuolization of Leydig cells due to fat accumulation. Conclusions: SF-1/NR5A1 mutations are frequently found in 46, XY DSD individuals (9%) and manifest with a broad phenotype. Testes histology is characteristic for fat accumulation and degeneration over time, similar to findings observed in patients with lipoid congenital adrenal hyperplasia (due to StAR mutations). Genotype-structure-function-phenotype correlation remains elusive. (J Clin Endocrinol Metab 97: E1294-E1306, 2012)
Keywords: STEROIDOGENIC FACTOR-I; XY GONADAL-DYSGENESIS; DNA-BINDING DOMAIN; GLY146ALA POLYMORPHISM; HETEROZYGOUS MUTATION; ADRENAL INSUFFICIENCY; FACTOR-1; SF-1; PATIENT; SF1